Hubungan Kualitas Tidur Dengan Tingkat Stres Mahasiswa Keperawatan Yang Menjalani PKL Di Rumah Sakit Advent Bandung - Peranginangin, Miliyanti Cindy Lowsa; Rantung, Jeanny (Innovative: Journal Of Social Science Research, 2024)
Nursing students of Universitas Advent Indonesia are required to participate in Field Work Practice. Where this activity requires students to be able to work and meet academic demands, this provides changes in student activates and has an impact on their sleep quality. This study was conducted on 71 nursing students who had participate Field Work Practice at the Rumah Sakit Advent Bandung (RSAB) starting from level 2 students to professions. This study used a descriptive analysis research method and a Cross Sectional method to measure both variables. With a questionnaire measuring instrument to determine whether there is a relationship between sleep quality and stress level of nursing students undergoing Field Work Practice at Rumah Sakit Advent Bandung (RSAB). The results of this study found that most students had poor sleep quality and experienced low stress levels with a figure of 97.2%. However, there was no relationship between sleep quality and stress levels experienced by nursing students of Universitas Advent Indonesia who underwent Field Work Practice at the Rumah Sakit Advent Bandung (RSAB).